Socio-legal implications of cross-border marriage among Muslims in Malaysia: an empirical study - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Wok, Saodah; Che Soh @ Yusoff, Roslina (IIUM Press, International Islamic University Malaysia, 2019)
Marriage is a sacred bond between a man and a woman. Such a relationship is blessed by Allah as is mentioned in the Qur’an and the traditions (Sunnah) of the Prophet (PBUH). The laws created by man are meant to streamline the conduct of marriage, apart from thealready provided ḥukm laid down in Islam. There are peoplehowever who violate these laws due to their own ignorance and thisviolation affects the future of the marriage as well the people who areinvolved in it. A cross-border marriage is a marriage conductedwithout permission from the registrar of marriage in each State andits solemnisation can be contracted in Malaysia or outside Malaysia.The purpose of this study is to examine and analyse the differences inthe demographic information respondents have with regard to theimplications of cross-border marriage among Muslims in Malaysia.The sample consists of four hundred respondents from four regionsin Malaysia. A survey using a questionnaire was the main method ofcollecting data. To support the empirical evidence, a semi-structuredinterview was also conducted in the study. The research reveals thateven though the respondents were aware of the implications ofcross-border marriage, a new mechanism is still required to controlthe occurrence of this type of marriage as it affects the people whoare involved, especially the women and children.